The Possibility of Using the Fresh Water Bivalve, Spathopsis Rubens, in The Nile River, El Mahmoudia Water Stream as Bioindicator For Pollution - E, H Radwan; A, Abdel Mawgood; A, Z Ghonim; R, El Nagar (International Journal of Limnology, 2018)
Bivalves are used as bioindicators of heavy metals pollution because they are known to concentrate these elements, providing a time integrated indication of environmental contamination. Trace metals can reach high concentrations in sediments and also in aquatic organisms by bioaccumulation through the food chain. Six heavy metals (Hg, Zn, Pb, Fe, Mg and Cu) were collected and investigated from Abu Hummus, El Behara. The concentration of Hg was high in winter as 2.3µg/g in sediment. The Zn concentration was high in summer in sediment as 8.1µg/g. The Pb concentration was high in winter in water as 3.3µg/l. The concentration of Fe in sediment was high in summer as 492 µg/g. The concentration of Mg was high in sediment as 408µg/g. The concentration of Cu was high in summer in sediment as 301µg/g. The mean concentrations of Fe in the present study are within the permissible limits of law 48/1982 (<1 mg/l) and the guideline of (WHO, 1993) which is <1 mg/l. The mean concentration level of copper is within the permissible limits of law 48/1982 (<1.0 mg/l). The mean levels of the heavy metals (Hg, Zn, Pb, Fe, Mg and Cu) detected in the present study in the water stream are less than the permissible limits recommended by (USEPA, 2005). In the present study there is a significance between all seasons in the protein content in the soft tissue of Spathopsisrubensas the mean concentration level in Spring was reported as 102.83mg/g which is higher then that of autumn 100.5mg/g, summer 93.33 mg/g and winter 80.50 mg/g. In the present study the mean activity level of GPx in spring was higher than the other seasons such as spring 31.33u/g ˃ summer 28.33 u/g ˃Autumn 26.67 u/g ˃ winter 20.50u/g. The mean activity level of SOD in summer was higher than the other seasons such as summer 38.83 u/g ˃ spring 33.33 U /g ˃Autumn 28.83U/g ˃ winter 22.83U/g. The mean activity level of CAT in spring was higher than the other seasons such as spring 25.67u/g ˃ summer and autumn19.83u/g ˃ winter 15.17u/g. The mean activity level of MDA in winter was 30.50 U/g ˃ summer 22.50U/g ˃ autumn 18.0 U/g ˃ spring 16.83U/g. In the present study it was found that the mean activity level of MDA increased in winter at the same time the mean activity level of CAT, SOD and GPx were decreased in winter. Negative correlation was reported between CAT and Hg in winter as r=-0.88*. A positive correlation coefficient in winter was found between SOD activity level and CAT activity level as r=0.838*.
Keywords: Bivalve-heavy metals-fresh water-Abo Homous-ElMahmoudia stream.